Tilted- and axial-beam formation by a single-arm rectangular spiral antenna with compact dielectric substrate and conducting plane. - Nakano, H. (IEEE Transactions on antennas and propagation)
A single-arm rectangular spiral antenna is analyzed using the finite-difference time-domain method. The spiral is printed on a finite-size dielectric substrate backed by a finite-size conducting plane. Both the substrate and conducting planes are square with a side length L of less than 0.6λ0 (λ0: wavelength in free space). The radiation pattern is dependent on the outermost arm peripheral length C. The spiral whose peripheral length is within 2λg<C<3λg (λg: the guided wavelength of the current) radiates a tilted beam of circular polarization. When the peripheral length is decreased to λg<C<2λg, the spiral radiates an axial beam. The axial beam has a wide half-power beam width of approximately 102° (for L≈0.369λ0) with a gain of approximately 6.7 dB. The axial beam shows a 15% frequency bandwidth for a 3 dB axial ratio criterion. Over this bandwidth, the voltage standing-wave ratio (VSWR) is less than two, as desired. The experimental results for the radiation pattern, gain, axial ratio, and VSWR are also presented